RANCANG BANGUN ALAT UJI PERKOLASI TANAH BERBASIS ARDUINO - Aryani, Dharma; Jusriadi, Jusriadi; Ifdal, Fahrul (Jurnal Teknologi Elekterika, 2023)
Water absorption testing through soil percolation test is mostly handled manually. During the testing process, it still requires many people to supervise it, and the reading error rate is still high. Therefore, a measuring instrument that works automatically is needed that can more specifically read the rate of water absorption into the soil accurately. In this final project, the tool is made using Arduino Mega, HC-SR04 ultrasonic sensor, 128x64 LCD, buzzer, NEO6MV2 GPS Module, RTC (Real Time Clock), push button, and Lithium-Ion Battery. The result of this final project is a soil permeability measuring instrument that can accurately measure the rate of water infiltration. Based on the results of design, testing and analysis of the design results, a soil permeability measuring instrument is obtained that can properly measure the rate of water infiltration